Hartnup Disease Masked by Kwashiorkor (Journal of Health, Population and Nutrition, 2010)
This report describes an 11-month old girl with Hartnup disease presenting with kwashiorkor and acrodermatitis enteropathica-like skin lesions but free of other clinical findings. This case with kwashiorkor had acrodermatitis enteropathica-like desquamative skin eruption. Since zinc level was in the normal range, investigation for a metabolic disorder was considered, and Hartnup disease was diagnosed. Key words: Acrodermatitis; Case studies; Hartnup disease; Kwashiorkor; Turkey DOI: 10.3329/jhpn.v28i4.6049 J HEALTH POPUL NUTR 2010 Aug;28(4):413-415